El cibersexo, fenómeno contemporáneo de la cibercultura en jóvenes universitarios (2019)
Sexuality is a determining part of the human being, the way in which it manifests has varied from time to time and is currently the protagonist in the virtual scene. Through the internet it is possible to chat for sexual purposes, find erotic material, contact people and establish uncensored relationships; online activities that are part of the repertoire of the so-called cybersex. This research aimed to examine the way in which young university students perceive and experience it, gathering 64 university students in interviews and focus groups, between 18 and 25 years. The analysis of the results shows the way in which cyberculture is giving form and content to behaviors, to experiences, determining aspects of the subjects such as their identity, their possibilities of experiences and their relationships. It could be concluded that cyberculture is currently influencing sexual acts, since it is fostering a wide variety of possibilities for eroticization and excitement, also becoming learning spaces since cyberpornography has been meeting this need. Due to the rise of pages with erotic and sexual content and the frequency with which they interact with them, it is important to broaden their understanding of when that use becomes a true addiction, and identify the factors that can act as risk factors and protection in addiction to new technologies.